2014
DOI: 10.1371/journal.pone.0111367
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Antigens rLipL21, rLoa22, rLipL32 and rLigACon4-8 for Serological Diagnosis of Leptospirosis by Enzyme-Linked Immunosorbent Assays in Dogs

Abstract: Animal leptospirosis is one of the most common zoonotic diseases in the United States and around the world. In a previous study, we applied four recombinant antigens, rLipL21, rLoa22, rLipL32 and rLigACon4-8 of Leptospira interrogans (L. interrogans) for the serological diagnosis of equine leptospirosis (Ye et al, Serodiagnosis of equine leptospirosis by ELISA using four recombinant protein markers, Clin. Vaccine. Immunol. 21:478–483). In this study, the same four recombinant antigens were evaluated for their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…The emergence of leptospirosis world-wide resulted in an increased demand for safe, standardized and validated diagnostic methods for the diagnosis of leptospirosis (20) (14). The development of recombinant proteins is one approach that is suitable for the safe production of high quality ELISA reagents given that are easily expressed, produced and standardize with high degree of consistency between batches without the biosecurity risks associated extraction of leptospiral antigen from pure microbiological culture preparations (6, 20). Here, we developed an ELISA based on a baculovirus recombinant LipL32 protein with potential application as diagnostic antigen in an indirect ELISA system for detection of antibodies in dogs plasma samples.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The emergence of leptospirosis world-wide resulted in an increased demand for safe, standardized and validated diagnostic methods for the diagnosis of leptospirosis (20) (14). The development of recombinant proteins is one approach that is suitable for the safe production of high quality ELISA reagents given that are easily expressed, produced and standardize with high degree of consistency between batches without the biosecurity risks associated extraction of leptospiral antigen from pure microbiological culture preparations (6, 20). Here, we developed an ELISA based on a baculovirus recombinant LipL32 protein with potential application as diagnostic antigen in an indirect ELISA system for detection of antibodies in dogs plasma samples.…”
Section: Discussionmentioning
confidence: 99%
“…Concordance rate experiments showed that the ELISALipL32 was capable to detect more (57/57) samples positive for antibodies to rLipL32 that the RTPCR (45/57) reference method. This can be explained because of the fact that after infection, Leptospira rapidly proliferates in the blood stream producing an acute phase that lasts for about 10 days when molecular diagnosis is capable to produce a positive result (20). On the other hand, antibodies can be detected in blood by the 6 th to 10th day post infection, which coincides with the clearance of Leptospira from the blood stream.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After incubation at 30°C for 2 hours, the antiserum was performed for agglutination using dark field microscopy. Final titers represent the reciprocal of the highest serum dilution showing at least 50% agglutination of antigen in the suspension [29]. …”
Section: Methodsmentioning
confidence: 99%